Pengaruh Motivasi Kerja, Reward Dan Punishment Terhadap Kinerja Karyawan (Studi Kasus CV. Avindo Mandiri) - Ahmad Afini Maulaya; Muhammad Mansur; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This study aims to determine the effect of work motivation, reward and punishment on employee performance. The research used is descriptive quantitative method. The population in this study are employees of CV. Avindo Mandiri. The data used are secondary data and primary data by using a questionnaire technique. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. The results of the study simultaneously obtained the results that the characteristics of work motivation, reward and punishment have a significant effect on employee performance, work motivation variables have a positive and not significant effect on employee performance, the reward variable has a positive and significant effect on employee performance and the punishment variable partially has a positive and significant effect on employee performance Keywords: Work Motivation, Reward, Punishment, Employee Performance